Regulation of Neural Stem Cell Proliferation and Differentiation by Graphene-Based Biomaterials. (16th October 2019) - Xia, Lin; Zhu, Wenjuan; Wang, Yunfeng; He, Shuangba; Chai, Renjie
Abstract : The transplantation of neural stem cells (NSCs) has become an emerging treatment for neural degeneration. A key factor in such treatments is to manipulate NSC behaviors such as proliferation and differentiation, resulting in the eventual regulation of NSC fate. Novel bionanomaterials have shown usefulness in guiding the proliferation and differentiation of NSCs due to the materials' unique morphological and topological properties. Among the nanomaterials, graphene has drawn increasing attention for neural regeneration applications based on the material's excellent physicochemical properties, surface modifications, and biocompatibility. In this review, we summarize recent works on the use of graphene-based biomaterials for regulating NSC behaviors and the potential use of these materials in clinical treatment. We also discuss the limitations of graphene-based nanomaterials for use in clinical practice. Finally, we provide some future prospects for graphene-based biomaterial applications in neural regeneration.